(untitled) (Indian Journal of Animal Production and Management, 2025)
Comparatively examining the histological and structural traits of the pancreas in Gallus gallus domesticus and Gallinula chloropus was the aim of current study. This study’s main objective was to evaluate these bird species’ value as reliable suppliers of chicken and eggs. The birds samples are divide for two groups first group was five laying hens and second group was five moorhen assigned to anatomical study and histological study. In laying chickens, the pancreas was distinguished by its white, pinkish coloration while in Gallinula chloropus was characterized by its white to pinkish coloration. Histologically speaking, it seems that the Moorhen bird’s connective tissue capsule was relatively thinner than that of the Laying hens. The connective tissue capsule, which extends from the septa to the pancreatic parenchyma, is less common in moorhens than laying hens. Both birds’ exocrine glands contained serous tubulo-acinar glands. The secretory acini of the Laying hens possessed pyramid-shaped acinar cells. The presence of oval, elongated acinar cells was a characteristic of the moorhen bird’s secretory acinar.